2014
DOI: 10.1039/c3dt53408a
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photoluminescence in CaMoO4:Eu3+ by Gd3+ co-doping

Abstract: We have studied the luminescence property of CaMoO4:Eu(3+). The emission peaks at 590 ((5)D0→(7)F1) and 613 nm ((5)D0→(7)F2) for Eu(3+) are observed after excitation at 266 nm (i.e. Mo-O charge transfer band). The peak intensity of the latter dominates over the former indicating an asymmetric environment of Eu(3+) in EuO8 polyhedron or parity mixing. Luminescence intensity increases significantly with co-doping of Gd(3+). This is ascribed to energy transfer from Mo-O/Gd(3+) to Eu(3+). Luminescence intensity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(65 citation statements)
references
References 53 publications
3
62
0
Order By: Relevance
“…4 itself. The s value is found to be $467 ls, which is well matches with the reputed value in the literature [12]. Singh et al found that on indirection excitation (Mo-O CTB) a modified bi-exponential equation (having diffusion and energy transfer parameter) shows good fitting instead of mono-exponential fitting [9].…”
Section: Pl Decay Studiessupporting
confidence: 73%
See 1 more Smart Citation
“…4 itself. The s value is found to be $467 ls, which is well matches with the reputed value in the literature [12]. Singh et al found that on indirection excitation (Mo-O CTB) a modified bi-exponential equation (having diffusion and energy transfer parameter) shows good fitting instead of mono-exponential fitting [9].…”
Section: Pl Decay Studiessupporting
confidence: 73%
“…5 D 2 and 7 F 0 ? 5 D 1 intra-configurational f-f transitions of Eu 3+ ions [11,12]. Moreover, Eu-O, Mo-O CTB and Gd 3+ bands are overlapped between 200 and 350 nm giving a glimpse of energy transfer from Gd/Mo-O to Eu 3+ excited state.…”
Section: Excitation Studiesmentioning
confidence: 95%
“…10. These decay times are found to be single exponential for all the concentrations of Eu 3+ ions, which are similar to these observed for Eu 3+ -doped YAl 3 (BO 3 ) 4 :Eu 3+ /Tb 3+ [35], PKBA:Eu 3+ [36], CaMoO 4 :Eu 3+ [37] and CaMoO 4 :Eu 3+ /Gd 3+ [38] phosphors. The experimental lifetimes (s exp ) of 5 D 0 level determined by taking the first e-folding times of the intensities are 2.69, 2.59, 3.53 and 3.63 ms for Na 3 Gd(PO 4 ) 2 :0.5Eu 3+ , Na 3 Gd(PO 4 ) 2 :1.0Eu 3+ , Na 3 Gd(PO 4 ) 2 :1.5Eu 3+ and Na 3 Gd(PO 4 ) 2 :2.0Eu 3+ phosphors, respectively.…”
Section: Luminescence Decay Analysissupporting
confidence: 73%
“…Since Kroger concluded that the lattice group (WO 4 2− /WO 6 6− ) itself was responsible for the luminescence origin4, what influenced tungstates luminescence properties was explored extensively such as morphology, size and dimension56. In addition to intrinsic emission of anion-cation groups, there was also emission from defect states, inevitably incurred because of the abundant synthesis methods and flexible annealing temperatures and atmospheres789. For example, the photoluminescence intensity of amorphous BaWO 4 was higher than that of crystalline BaWO 4 because of different annealing temperatures10.…”
mentioning
confidence: 99%